Breaking the cycle of Xanthomonas campestris pv. musacearum in infected fields through the cultivation of annual crops and disease control in adjacent fields - Rutikanga, A.; Sivirihauma, Charles; Ocimati, W.; Night, G.; Murekezi, C.; Ndungo, V.; Mugiraneza, T.; Rurangwa, E.; Blomme, Guy (Wiley, 2016)
Cultivation of non‐host crops after uprooting Xanthomonas campestris pv. musacearum (Xcm)‐infected banana plants has been advocated for breaking Xanthomonas wilt disease (XW) cycle in fields. Knowledge on the interaction of these crops with Xcm is limited. Maize, beans and sweet potato were planted after uprooting Xcm‐infected banana plants in Rwanda and eastern Democratic Republic of Congo (DR Congo). A weed fallow (mixed species) served as the control. After one, two and/or four break‐crop or fallow seasons, healthy plantlets were replanted and monitored for XW for 12–24 months. XW status in adjacent fields was monitored, and diseased stems within 100–300 m radius of the two‐ and four‐season experiments were uprooted. In Rwanda, soil and plant parts from the one‐season experiments were sampled for Xcm isolation and Xcm‐like colonies confirmed with Xcm‐specific primers using PCR. Pathogenicity tests were performed to confirm the ability of the PCR‐positive isolates to infect healthy banana plantlets. XW was observed in all the one‐season experiments, with higher cumulative incidences in maize and bean plots. However, no similar trends were observed in the two‐season experiments, with a 6–8% incidence observed only in bean and potato plots in DR Congo. Lengthening time under break crops to two and four seasons, respectively, reduced the incidence to 3% and zero in Rwanda and 0–8% in the two‐season experiments in DR Congo. Incidence in the first‐season experiments highly correlated (R = 88) to that in the adjacent fields, suggesting possible re‐infections from these fields. Two season with break crop plus collective XW control are recommended in these agro‐ecosystems. PCR‐positive Xcm‐like colonies from break crops only induced localized cell death on banana, while PCR‐positive isolates from symptomatic banana plants caused full XW symptoms. Cross‐infection/inoculation studies under controlled conditions are still needed to conclusively elucidate Xcm interaction with these crops.